Virtual reality as a potential therapy in a rehabilitation sanatorium for patients after ischemic stroke: impact on quality of life and social participation—a randomized trial - Dabrowská, Marcela; Honzíková, Lucie; Pastucha, Dalibor; Janura, Miroslav; Tomášková, Hana; Fiedorová, Iva; Čechová, Šárka A.; Trdá, Jana; Elfmark, Milan (Frontiers in Rehabilitation Sciences, 2025)
ObjectiveThe aim of this study was to determine whether adding virtual reality therapy to conventional rehabilitation improves the quality of life, cognitive functions, and social participation of patients after an ischemic stroke.DesignRandomized controlled study conducted in a rehabilitation center.ParticipantsThe experimental group with therapy in virtual reality included 25 patients (age 59.4 ± 8.9 years), and the control group with conventional therapy consisted of 25 patients (age 63.0 ± 8.8 years). Inclusion criteria for the study were: age 40–79 years, stable condition, Mini-Mental State Examination >25 points, intact vision, preserved grip function of the thumb and index finger of the affected limb, functional mobility according to the functional ambulatory category (FAC) 3–5, and no other neurological disease.MethodsThe Mini Mental State Examination, the Barthel Index, the Extended Barthel Index, and the WHO Disability Assessment Schedule 2.0 were used to assess cognitive function, quality of life, and self-sufficiency. Based on the results of normality test were used: t-test for two samples (age, time since stroke), the chi-square test (gender), nonparametric paired Wilcoxon test and Mann–Whitney U test. Friedman analysis was used to analyze repeated measures and a post hoc test Scheffe test was used to compare differences. Statistical tests were evaluated at the 5% significance level.ResultsNo significant differences were found between the experimental and control groups in any of the tests applied after treatment. Significant differences emerged after treatment in all WHODAS domains studied for each group compared to the measurement before therapy. In the experimental group, the positive effects of therapy persisted 1 year after the end of therapy compared to the measurement before therapy.ConclusionsVirtual reality has proven to be a suitable adjunct to conventional therapy for post stroke patients and offers an advantage over traditional rehabilitation methods in that it allows training in activities of daily living that are not commonly available in a hospital setting.